Pengaruh Pajak dan Belanja Modal Terhadap Pertumbuhan Ekonomi (Data Panel di Provinsi Kalimantan Timur) - Maisya Auliandhana; Khairul Amri (Jurnal Ekonomi Manajemen dan Sekretari, 2023)
This study aims to see the effect of tax revenue and capital expenditure on economic growth in East Kalimantan. The data used is panel data of 8 districts and cities in East Kalimantan during the period 2013 to 2020. The data analysis equipment used is fixed-effect method panel regression, then continued with panel vector autoregression (PVAR) analysis. The results found that economic growth in a particular period was significantly influenced by economic growth in the previous period. Capital expenditure in a particular period is also significantly influenced by capital expenditure in the previous period. Taxes do not have a two-way causality relationship with economic growth and capital expenditure does not have a two-way causality relationship with economic growth. However, there is a one-way causality relationship between taxes and capital expenditure.